1990
DOI: 10.1111/j.1471-0528.1990.tb02498.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of platelet behaviour and thromboxane production in whole blood in normal pregnancy and the puerperium

Abstract: Summary. A longitudinal study of platelet behaviour (platelet aggregation and release reaction) in whole blood and of serum thromboxane B2 production was performed before, during and after normal pregnancy. The response of platelets to arachidonic acid and to adrenaline was significantly increased in the third trimester. Six weeks after delivery, values were still modestly increased but return to non‐pregnant values was complete by 12 weeks. Serum thromboxane B2 production was unchanged throughout pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 18 publications
2
48
1
Order By: Relevance
“…3 During normal pregnancy platelet aggregation and secretion of ATP is increased compared with the non-pregnant individuals, reaching a prominent peak in the third trimester but returning to normal by 6-12 weeks post-partum. 4,5 Platelet binding to fibrinogen remained unchanged. 5,6 Fitzgerald et al indicated an elevated biosynthesis of thromboxane during pregnancy.…”
Section: Introductionmentioning
confidence: 82%
“…3 During normal pregnancy platelet aggregation and secretion of ATP is increased compared with the non-pregnant individuals, reaching a prominent peak in the third trimester but returning to normal by 6-12 weeks post-partum. 4,5 Platelet binding to fibrinogen remained unchanged. 5,6 Fitzgerald et al indicated an elevated biosynthesis of thromboxane during pregnancy.…”
Section: Introductionmentioning
confidence: 82%
“…All of these data raise the question of whether there is an increase in the thromboxane biosynthetic pathway during pregnancy. Ylikorkala and Viinikka [27] found that platelet thromboxane formation is increased in vitro during pregnancy; however, another report suggested that there is no change in vitro during pregnancy [12]. These reports indicate that platelet thromboxane production in vitro during pregnancy remains unclear and controversial.…”
Section: Introductionmentioning
confidence: 69%
“…Increased platelet aggregation has been demonstrated in platelet-rich plasma (PRP) and in whole blood using various agonists such as adenosine 5)-diphosphate (ADP) and arachidonic acid (AA) [12,17,18]. The formation of thromboxane A 2 (TxA 2 ) in platelets is reported to increase in pregnancy [6,27].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet hyperaggregation during third trimester was reported in a number of studies suggesting hyper functioning platelets near labor [38][39][40] . Recently reduced platelet aggregation was observed using a modified technology in light transmission aggregometry [41].…”
Section: Qualitative Changes In Platelets and Activation Markersmentioning
confidence: 99%